The effect of avoiding school activities and lack of parental involvement on young sexual minorities’ mental health - Úlfar Viktor Björnsson 1993- (2021)
Studies have suggested that depressive symptoms and low self-esteem are on the rise amongst non-heterosexual young people when compared to their straight, cis-gender counterparts. This study aimed to examine whether sexual minority youth in Iceland were more likely to develop depressive symptoms and lower self-esteem if they did not have strong parental involvement in their lives, or if they feel the need to avoid school activities due to feeling unsafe. The dataset was collected from a recent online study conducted by Samtökin ’78 (The National Queer Organization of Iceland) and GLSEN (Gay, Lesbian and Straight Education Network). The participants consisted of a total of 181 non-heterosexual Icelandic adolescents with the age range of 13-20 years old. Results indicated that non-heterosexual youth were more likely to experience depressive symptoms and have lower self-esteem if they felt the need to avoid school activities due to feeling unsafe. However, there was no significant difference between depressive symptoms or self-esteem by parental involvement. Longitudinal studies on the mental health of Icelandic non-heterosexual children and adolescents are suggested for future research. Keywords: Sexual minorities youth, depressive symptoms, self-esteem, parental involvement, school avoidance Rannsóknir hafa bent til þess að þunglyndi og lágt sjálfstraust fari vaxandi meðal ungra hinsegin einstaklinga í samanburði við gagnkynhneigða, sískynja jafnaldra þeirra. Þessi rannsóknarskýrsla miðar að því að kanna hvort hinsegin einstaklingar á Íslandi séu líklegri til þess að þróa með sér þunglyndi og lágt sjálfsálit ef þeir hafa ekki næg afskipti foreldra í lífi sínu eða ef þeir finna sig knúna til þess að forðast skólastarf af öryggisástæðum. Gögn voru fengin úr nýlegri netrannsókn sem Samtökin ’78 og GLSEN (Gay, Lesbian and Straight Education Network). Þátttakendur samanstóð af alls 181 hinsegin íslenskum ungmennum á aldursbilinu 13-20 ára. Niðurstöður bentu til þess að hinsegin ungmenni væru líklegri til þess að ...